CHAMBERS IN SLOVENIA – SO SIMILAR AND YET SO DIFFERENT; A COMPARISON OF STRUCTURES AND WORKING METHODS USING THE EXAMPLE OF THE VETERINARY CHAMBER AND THE DETECTIVE CHAMBER IN REPUBLIC OF SLOVENIA - Ožbalt Podpečan; Miha Dvojmoč (Slovenian Veterinary Research, 2024)
Chambers are associations of legal and natural persons engaged in profitable activity. By definition, they are a community governed by public law that is pursuing a similar activity, founded primarily to protect the interests of its members. In Slovenia, chambers are established to represent persons engaged in various business activities - from companies, sole traders, farmers, foresters, craftsmen, private detectives, veterinarians and similar. The chambers differ slightly from one another, and can essentially be divided into three groups, namely chambers of commerce, professional chambers and mixed-type chambers. The tasks of the chambers, their bodies and their duties, the criteria for membership as well as the termination, financing or acquisition of funds for operation and other important information are specified in their by-laws, the respective law or other legal act. In this article the entire system of chambers of the Republic of Slovenia is presented using the example of three randomly selected chambers that differ in terms of their functioning, the exercise of public powers or financing in general, with the Chamber of Veterinarians and the Detective Chamber being explained in more detail. We have selected these two chambers as we wanted to present one natural science and one social science chamber. In the comparison between the detective and veterinary chambers, we can therefore research and analyse many aspects that reflect the diversity and specificity of each professional field. One of the reasons, why we have chosen these two chambers is also the fact, that we as authors are or were active members of our two chosen chambers. The comparison makes it easier to understand how they work, as well as their similarities and differences.  We found that not only the chambers we selected, but most chambers operate very similarly, perform similar tasks and have many of the same organs required for their functioning. This is probably due to the fact that all chambers in Slovenia have developed or started to develop according to the model of the first chamber– the Chamber of Commerce and Industry of Slovenia.